Comparing Grubbs-, Werner-, and Hofmann-Type (Carbene)ruthenium Complexes: The Key Role of Pre-Equilibria for Olefin Metathesis - Adlhart, Christian; Volland, Martin A. O.; Hofmann, Peter; Chen, Peter (Helvetica chimica acta, 2000)
A gas‐phase comparison of intrinsic olefin metathesis rates for (carbene)ruthenium complexes by means of electrospray‐ionization tandem mass spectrometry reveals a reversal of the reactivity trends observed in solution. The solution‐phase ordering of reactivity is accordingly attributed to a more favorable pre‐equilibrium, producing the metathesis‐active species in the case of the Hofmann‐ and Werner‐type complexes relative to those of the Grubbs type.